Making sense of South African Mmega Dikgang’s transition from Setswana to English - Molale, Bright T.; Mpofu, Phillip (Routledge, 2022)
The importance of indigenous language press in disseminating development communication and promoting indigenous languages cannot be overstated. However, over the years, indigenous language newspapers have developed and collapsed. Salawu (2006, “Rich History, Uncertain Future,” Rhodes Journalism Review 26: 55–56) observes that, whilst in 1930 there were nineteen registered African language newspapers in South Africa, today, the majority of those newspapers are non-existent. However, the story of Mmega Dikgang, a community newspaper in North West Province, is fascinating. The publication has transformed from being an African language to an English language newspaper. Against this background, and using semi-structured interviews with the founder and editor and others affiliated with the newspaper, this study interrogates the development and transformation of the Mmega Dikgang community newspaper and is a vital contribution to understanding the development and sustainability of indigenous community language newspapers in South Africa.